The Implementation of Scientific Approach to Improve Mathematical Understanding Ability on Junior High School Students - Silvi Silvia; Aflich Yusnita Fitrianna; Heris Hendriana ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Mathematical understanding ability is a very important skill for students to achieve, because mastering mathematical involves more than just remembering formulas and knowing how to count, understanding concepts is also needed. But in reality, understanding skills are still low, students are still mostly fixated on existing formulas and examples given by the teacher. The purpose of this study was to see the improvement of mathematical understanding ability of VII students on Algebra material at Dharma Kartini Junior High School. This research uses classroom action research (CAR). The method used the spiral model of action research fromÂ Kemmis and McTaggart. The instrument used was a test instrument consisting of 10 questions of algebra material which was prepared based on the mathematical understanding ability of students whose learning used a scientific approach. This research was conducted in 2 cycles, each cycle consists of several stages starting from the planning, action, observation and reflection stages. The results of this study indicate that the aspects of students' mathematical understanding ability have increased as seen from the increasing percentage achievement on the question indicators after 2 learning cycles, namely in cycle I by 48% and cycle II by 78%. It is known that algebra material in class VII students of Dharma Kartini Junior High School can be influenced by the scientific approach with mathematical understanding ability. As more and more students showing understanding they can conclude and explain back what they have learned.